The whole truth and nothing but the truth? A case study comparing analytical and empirical assessments against site observations - Joaquim, A; Hartzenberg, AG; Gibbons, O; Coleman, T (Mine Closure 2021: Proceedings of the 14th International Conference on Mine Closure, 2021)
Canadian mining operations have been key contributors to economic vitality for a long time. The closure of historic mines can be challenging as often the level of information available is much less than active mines preparing to close. This paper uses a case study of a closed mine site to evaluate industry standard design methods against observed site conditions to assess the most suitable method to be applied for mine closure. This comparison is of importance as analytical methods and empirical assessment methods are becoming more advanced and are commonly used in the mining industry. It stresses the importance of evaluating results against site observations to assess the validity of results. This study focuses on Rock Mechanics and discusses the industry standard analytical methods used to assess the stability of the hanging wall and foot wall of the underground stope void, as well as the empirical method used to assess the stability of the crown pillar. The results from these methods are then compared to stability observations using bathymetric and three-dimensional sonar surveys collected of the historic mine workings. The information attained from the assessments is compared to the stability observations to confirm if evidence of the expected potential failure mechanisms exists at this historic mine site